2020
DOI: 10.1111/1753-0407.13109
|View full text |Cite
|
Sign up to set email alerts
|

Association between processes of diabetes care and health care utilization in patients with diabetes: Evidence from a nationally representative US sample

Abstract: Background: This study examined the association between quality of processes of diabetes care in terms of adherence to American Diabetes Association (ADA)recommended guidelines and health care utilization in patients with diabetes. Methods: Adults with diabetes were identified from the pool of five panels of the Medical Expenditure Panel Survey, a nationally representative US sample, between 2012 and 2017. The Diabetes Care Survey was used to determine adherence to the ADA-recommended guidelines for processes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…The ACA is of great importance in population health for individuals with diabetes because uninsured persons tend to have worse diabetes control and are less likely to achieve the recommended processes of diabetes care. 53 , 54 Although we did not explicitly test for the association of the implementation of the ACA with the rates of ED, we did not observe any visually discernible evidence of an association between rates of ED use and policy nationally or by state in our analysis of rates by payer. Eligibility expansions, growing inequality, and the lingering effects of the Great Recession are also reflected in our reported trends.…”
Section: Discussionmentioning
confidence: 71%
“…The ACA is of great importance in population health for individuals with diabetes because uninsured persons tend to have worse diabetes control and are less likely to achieve the recommended processes of diabetes care. 53 , 54 Although we did not explicitly test for the association of the implementation of the ACA with the rates of ED, we did not observe any visually discernible evidence of an association between rates of ED use and policy nationally or by state in our analysis of rates by payer. Eligibility expansions, growing inequality, and the lingering effects of the Great Recession are also reflected in our reported trends.…”
Section: Discussionmentioning
confidence: 71%
“…People with diabetes are more likely to be admitted to inpatient care than people without diabetes [ 6 ]; the CDC reports that 339 out of 1000 people with diabetes may experience the need for inpatient care over a 1-year period [ 1 ]. Fortunately, regular PCP visits may reduce the risk of inpatient care, as following American Diabetes Association guidelines is associated with decreased admission rates [ 11 ]. Because the Precision Nudging intervention focused on the unengaged population who were out of compliance with the recommended cadence of primary care visits, we focused on only that group in calculating potential inpatient care costs.…”
Section: Methodsmentioning
confidence: 99%
“…Noncompliance with recommended care has serious consequences for both individuals and systems. A comparison of people with diabetes who were compliant and noncompliant with American Diabetes Association recommendations for primary care found significant improvements in medical utilization, including a reduction in the need for inpatient care [ 11 ] when recommendations were followed. For example, one study found that promoting lifestyle changes around diet and physical activity for people with diabetes and prediabetes yielded significant cost savings related to medical care over a 10-year time period [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the implementation of medical standards, such as guidelines, by patients is highly unsatisfactory. Compliance with current diabetes guidelines is low, with rates ranging from 7.8% to 34.1% [11,12]. It has been suggested that this may be because the guidance provided by medical standards lacks a life perspective and is somewhat detached from the daily needs of patients.…”
Section: Introductionmentioning
confidence: 99%